Welcome to the SA Heart® Congress 2025 - Vachiat, Ahmed (SA Heart Journal, 2025)
We would like to welcome all our colleagues in the cardiology community to the 25th Annual SA Heart® Congress in Johannesburg. This year's theme is "unifying hearts and minds". With this shared vision, we wish to expand our knowledge of the link between heart and mind in the everevolving field of cardiology. The congress will take place at the Sandton Convention Centre in Johannesburg from 17 to 19 October 2025.